Can Authentic Leadership Increase Volunteerism in Fire Disaster Management? - Firda Hidayati (Brawijaya University, 2022)
There is few researchers study on factors to influence volunteer to dedicate on the collaboration in fire disaster management which shape more effective fire disaster management. Interestingly, we found that although the fire disaster management is managed under a small unit, the outcomes of the Magelang District fire prevention technical unit are overwhelming. The key is authentic leadership to shape community involvement and volunteerism as well as government officials and private sectors to join collaboration. The leader introduced the incentive to join the collaboration as well as institutional arrangement both internal and external institutions that in the short term push significant trust to enhance the effectiveness of fire disaster management. It is the persistence, example and risk taking as well as personal knowledge on fire management and regulation of the head of unit that lead to eagerness of the volunteers to work beyond duty.